Comparative study on the isothermal aging of bare Cu and ENImAg surface finish for Sn-Ag-Cu solder joints - M.A., Rabiatul Adawiyah; O., Saliza Azlina (ScienceDirect, 2018)
The surface finish of electroless nickel/immersion silver (ENImAg) has been developed as an alternative to lead-free surface finish in electronic industry for the reduction of metal cost without affecting the reliability and solderability performance. In this study, different types of lead-free solders, Sn-3.0Ag-0.5Cu (SAC305) and Sn-4.0Ag-0.5Cu (SAC405) were involved along with ENImAg and bare copper substrate in order to investigate the formation of intermetallic compounds (IMCs) under reflow and aging time. The characterization and analysis of the samples conducted through scanning electron microscopy and energy dispersive x-ray. As a result, the IMCs of SAC/Cu which were formed on the interface were Cu6Sn5 and Cu3Sn. Unlike the reaction displayed by SAC/Cu, the IMCs of SAC/ENImAg which were formed on the interfaces, were identified as (Cu,Ni)6Sn5) and (Ni,Cu)3Sn4. The kinetic growth of each IMC was analyzed. It was found that IMC of SAC/Cu was thicker than IMC of SAC/ENImAg. Upon the revelation of these observations, ENImAg surface finish reduced the growth of IMC and smaller grains size compared to bare Cu.